Strategy for Soil, Water and "Wasteland" Resource Development in the Deccan Plateau and Hills-Technical Issues, Financial and Administrative Aspects - Bali, J.S. (Journal of Soil and Water Conservation, 2022)
A brief but comprehensive problem identification for the Agro clinmtic Zone No. 9 covermg the Deccan States has been followed by the critical appraisal of bast efforts. While outlining the Strategy for development of all types of land on the basis of watersheds, special thrust was on, micro water resources development, agro-industrial watersheds based on biomass produced and empowering of peoples organisations for financial and other decisions and pmviding financial & technological support to these bodies.